Midwifery Students Training in Oral Care of Pregnant Patients: an Interventional Study - Mohebbi, Simin Zahra (J Dent (Tehran), 2014)
OBJECTIVE: Midwives may play an important role in oral health promotion of pregnant women, whom they are in close contact with. Our aim was to evaluate an educational intervention on the oral health attitude and practices among the junior midwifery students of Tehran University of Medical Sciences in 2010. MATERIALS AND METHODS: The junior midwifery students were divided into intervention (n=29) and control (n=33) groups. The intervention group was first educated about general oral health, oral hygiene practices during pregnancy, and tooth brushing and flossing on models. Subsequently, the students performed role playing to ensure they understood the aforementioned lessons correctly. Before and three months after the training course the students filled out a validated self-administered questionnaire and a simplified plaque index was recorded. Statistical analysis was done by Mann-Whitney test and linear regression models. RESULTS: Before the intervention, the mean scores of attitude in general oral health for the intervention and control groups were 5.8 and 5.4, respectively, which improved to 8.9 and 5.4 after the intervention (P<0.001). The mean score of oral health attitude in pregnancy was 20.4 in the intervention group and increased to 30.9 (P<0.001). The intervention group demonstrated much better oral health practices in pregnancy and lower plaque index score after the intervention. CONCLUSION: The promising finding about attitude and practice improvement in midwifery students after participating in a short course on oral health promotion in pregnancy shows the necessity to enrich their training program by including this subject.